1995
DOI: 10.1016/0896-6273(95)90062-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of midbrain dopaminergic neurons by Sonic hedgehog

Abstract: Midbrain dopaminergic neurons, whose loss in adults results in Parkinson's disease, can be specified during embryonic development by a contact-dependent signal from floor plate cells. Here we show that the amino-terminal product of Sonic hedgehog autoproteolysis (SHH-N), an inductive signal expressed by floor plate cells, can induce dopaminergic neurons in vitro. We show further that manipulations to increase the activity of cyclic AMP-dependent protein kinase A, which is known to antagonize hedgehog signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
246
2
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(260 citation statements)
references
References 45 publications
8
246
2
4
Order By: Relevance
“…A current model holds that hedgehog activates decapentaplegic and wingless expression in wing and leg disks by reversing a tonic PK A-mediated inhibition of these genes (Felsenfeld and Kennison, 1995;Jiang and Struhl, 1995;Li et al, 1995;Strutt et al, 1995;Hammerschmidt et al, 1996). Data from vertebrate studies also support this model: the SHH-mediated induction of dopaminergic neurons in the ventral mesencephalon was blocked by increasing the level of PK A activity with forskolin or 8-bromo-cyclic AM P (cAM P) (Hynes et al, 1995). Previous work from our lab has shown that dibuturyl-cAMP, 8-bromocAM P, or forskolin inhibited proliferation in retinal progenitor cells (Taylor and Reh, 1990).…”
Section: Shh Acts As a Mitogen For Retinal Progenitorssupporting
confidence: 55%
See 1 more Smart Citation
“…A current model holds that hedgehog activates decapentaplegic and wingless expression in wing and leg disks by reversing a tonic PK A-mediated inhibition of these genes (Felsenfeld and Kennison, 1995;Jiang and Struhl, 1995;Li et al, 1995;Strutt et al, 1995;Hammerschmidt et al, 1996). Data from vertebrate studies also support this model: the SHH-mediated induction of dopaminergic neurons in the ventral mesencephalon was blocked by increasing the level of PK A activity with forskolin or 8-bromo-cyclic AM P (cAM P) (Hynes et al, 1995). Previous work from our lab has shown that dibuturyl-cAMP, 8-bromocAM P, or forskolin inhibited proliferation in retinal progenitor cells (Taylor and Reh, 1990).…”
Section: Shh Acts As a Mitogen For Retinal Progenitorssupporting
confidence: 55%
“…Because vertebrate and Drosophila eye development appear to require many of the same transcription factors, it is plausible that they would require some of the same cell-signaling molecules (for review, see Reh and Cagan, 1994). Second, in vertebrates, members of the Hedgehog family have been shown to act as inducing molecules for particular cell fates in spinal cord and mesencephalon (Roelink et al, 1994;Ericson et al, 1995;Hynes et al, 1995), and it is likely that these molecules play important roles in the overall patterning of the developing nervous system (Ekker et al, 1995b). Third, in vertebrates, Sonic hedgehog (Shh) expression in the zone of polarizing activity can be induced by retinoic acid (RA) (for review, see Johnson and Tabin, 1995), and recently we have reported that RA can act as a rod photoreceptor inducer in embryonic rat retinal cell cultures (Kelley et al, 1994.…”
Section: Abstract: Sonic Hedgehog; Indian Hedgehog; Desert Hedgehog;mentioning
confidence: 99%
“…Recently, the morphogen Sonic Hedgehog aminoterminal (ShhN) moiety 13 has been suggested to have neurotrophic and neuroprotective properties for dopaminergic neurons in vitro, since it was able to increase survival of these neurons in ventral mesencephalic cultures and protect them against MPP+ neurotoxicity. [14][15][16][17] Shh is a secreted neurodifferentiation factor that binds to a receptor complex, patched (ptc)-smoothened (smo).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a small percentage of sporadic medulloblastomas have mutations of Smoothened (SMO), a transmembrane protein that interacts with PTCH and is derepressed when Shh binds to PTCH (Dong et al, 2000;Zurawel et al, 2000;Taylor et al, 2002). Both familial and sporadic medulloblastomas with mutations of molecules in the Shh/PTCH pathway are typically of the desmoplastic histological variant (Hynes et al, 1995;Pietsch et al, 1997;Pomeroy et al, 2002).…”
Section: Developmental Mechanisms Promote the Growth Of Medulloblastomentioning
confidence: 99%